2018
DOI: 10.3390/ijerph15091904
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antidepressant Use on Healthcare Utilization among Individuals with Type 2 Diabetes and Depression Symptoms in the United States: Sociodemographic, Clinical, and Behavioral Factors Matter

Abstract: Individuals with diabetes are twice as likely to struggle from depressive symptoms than individuals without diabetes. However, this joint condition is undertreated in nearly two-thirds of patients. Failure to monitor the comorbidity may lead to suboptimal therapy. This study evaluated the association of antidepressant use with healthcare utilization in a national sample of patients with type 2 diabetes and depression symptoms in the United States. It further assessed the differences in sociodemographic, clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Our search yielded 14,389 unique abstracts, of which we assessed 96 full-text articles for eligibility, and selected nine studies for inclusion in the review [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] . Three studies used the same NHANES survey data [44] , and so, are expected to have significant duplication of participants: Binsalah 2018 was chosen for inclusion for the primary outcome, however, did not report data on individual antidepressant medications or classes, and so, Perez 2017 and Wang 2016 were included for this outcome, each reporting on a different exposure.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our search yielded 14,389 unique abstracts, of which we assessed 96 full-text articles for eligibility, and selected nine studies for inclusion in the review [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] . Three studies used the same NHANES survey data [44] , and so, are expected to have significant duplication of participants: Binsalah 2018 was chosen for inclusion for the primary outcome, however, did not report data on individual antidepressant medications or classes, and so, Perez 2017 and Wang 2016 were included for this outcome, each reporting on a different exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies identified depression through clinical coding in health or insurance records – two of these studies had the highest prevalence rates of 85% and 87% [36 , 40] ; the third had a relatively high prevalence rate of 0.57, however, this was recorded in a population of all-male military veterans [38] . The three studies with the lowest prevalence rates, ranging from 18% to 37% all identified depression in the community as part of the research study [35 , 41 , 43] . When combined in meta-analysis, these studies gave a pooled prevalence estimate of 29% (23% – 37%) and I 2 of 62%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations